Peranan Kepolisian Biak Numfor dalam Mengungkap Tindak Pidana - Ikbal Tawaqal (PPPM, Sekolah Tinggi Ilmu Hukum (STIH) Biak-Papua, 2021)
The purpose of this study was to determine the role of Biak’s Regional Police in revealing criminal acts in Biak’s jurisdiction and to know the handling of Biak’s identification police unit during criminal act investigations. This type of research is a field research. Data collection was carried out through interviews with predetermined sources and data collection related to using the object of research. The research data were analyzed descriptively. The results of the study indicate that the role of relevant officers is very important in terms of finding evidence. The factors of accuracy and education are very influential. Several processes are carried out in dealing with criminal acts: visiting and conducting site processing and collecting evidence. The coaching process is carried out in the correctional system and is placed in particular. The type of coaching carried out for correctional students includes mental and social skills development. The factors that hinder the legal protection of correctional students include the factors of place, human resources, expertise in handling prisoner students and cooperation between agencies.